Hadits Mawdhu' dan Bahayanya bagi Umat Islam - Anshory, Isa; Widyaningsih, Erna; Khotimah, Anisa Nur (TSAQOFAH, 2025)
Mawdu' hadith (false hadith) poses a significant threat to the authenticity of Islamic teachings, potentially leading the Muslim community astray. This study aims to identify the characteristics of mawdu' hadith, analyze the dangers of its spread, and provide recommendations to safeguard the authenticity of the Prophet Muhammad SAW’s hadith. The research employs a literature review method, examining both classical and contemporary texts on hadith sciences, as well as authoritative sources in the field of Qur'anic and hadith studies. The study finds that mawdu' hadith can distort the understanding of Islam, influence worship practices, and cause division within the community. Therefore, systematic efforts are needed to educate the public on the importance of hadith verification and enhance the understanding of hadith sciences. This research contributes to a better understanding of the crucial role of authentic hadith in preserving the purity of Islamic teachings and preventing the spread of teachings that deviate from the Prophet's guidance.